Labor Migration Effects on Alleviating Poverty for Rural Household: Empirical Evidence from China - Jitong Zhang; Fu, Xiaodong (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
This paper takes data from 31 provinces in China for 1986～2017 years as a sample, building a dynamic panel model and using systematic GMM estimation method to research the effect and mechanism of labor mobility on poverty alleviation. The results showed that poverty in the early stage had a significant impact on poverty in the current stage, and poverty had a significant time additive effect; There exists a negative dependence between labor mobility and poverty, labor flow does contribute significantly to poverty alleviation; Labor mobility indirectly promoted poverty reduction through two paths of income gap and agricultural development; The result of moderating effect shows that the improvement of transportation condition, industrial agglomeration is conducive to bring into play of poverty reduction of labor fluxion; From regional perspective, labor flow in the central region has the greatest poverty decreasing effect, the smallest in the eastern region. For that, we present some recommendations about decreasing poverty, such as reasonably guiding labor mobility, keeping away the recurrence and reproducibility of poverty and accelerating the melioration of traffic installation condition.